Balancing a genetic toggle switch by real-time feedback control and periodic forcing. Issue 1 (December 2017) - Lugagne, Jean-Baptiste; Sosa Carrillo, Sebastián; Kirch, Melanie; Köhler, Agnes; Batt, Gregory; Hersen, Pascal
Abstract Cybergenetics is a novel field of research aiming at remotely pilot cellular processes in real-time with to leverage the biotechnological potential of synthetic biology. Yet, the control of only a small number of genetic circuits has been tested so far. Here we investigate the control of multistable gene regulatory networks, which are ubiquitously found in nature and play critical roles in cell differentiation and decision-making. Using an in silico feedback control loop, we demonstrate that a bistable genetic toggle switch can be dynamically maintained near its unstable equilibrium position for extended periods of time. Importantly, we show that a direct method based on dual periodic forcing is sufficient to simultaneously maintain many cells in this undecided state. These findings pave the way for the control of more complex cell decision-making systems at both the single cell and the population levels, with vast fundamental and biotechnological applications. Cybergenetics aims to monitor and regulate cellular processes in real-time using computer monitoring and feedback of biological readouts. Here the authors use a feedback loop and periodic forcing to maintain cells with a bistable synthetic circuit near its unstable state.